Thrombosis and thrombocytopaenia after ChAdOx1 nCoV-19 vaccination: a single UK centre experience. Issue 7 (13th July 2021) - Bano, Fehmida; Badugama, Buddikha; Chandra, Deepak
Abstract : We report clinical findings of three patients presenting with thrombosis and thrombocytopaenia 10–16 days following the first dose of the ChAdOx1 nCoV-19 vaccine against SARS-CoV-2. All patients presented to a major university teaching hospital in the UK over a 5-day period and were found to have high-titre antibodies against platelet factor 4 (PF4) without previous exposure to heparin. All three patients presented with extensive venous thrombosis, significant thrombocytopaenia, elevated D-dimer and borderline low fibrinogen. Two had fatal intracerebral haemorrhage secondary to cavernous venous sinus thrombosis and one had PE. Reference laboratory testing of serum demonstrated anti-PF4 antibodies in all three patients. The clinical and laboratory findings confirmed vaccine-induced thrombotic thrombocytopaenia (VITT) which was poorly described at the time of presentation. We were able to manage successfully one patient with PE with intravenous immunoglobulin and corticosteroids.